Success and Failure of Technical Trading Strategies in the Cocoa Futures Market - Peter Boswijk; Gerwin Griffioen; Cars Hommes (Tinbergen Institute, 2001)
A large set of 5350 trend following technica! trading rules is applied to LIFFEand CSCE cocoa futures prices, and tothe Pound-Dollar exchange rate, in the period 1983:1-1997:6. We find that 72% ofthe trading rules generatespositive profits, even when correcting for transaction and borrowing costs, whenapplied to the LIFFE cocoa futuresprices. Moreover, a large set of trading rules exhibits statisticallysignificant forecasting power of the LIFFE cocoafutures series. On the other hand the same set of strategies performs poor onthe CSCE cocoa futures prices, withonly 18% generating positive net profits and hardly any statisticallysignificant forecasting power. The largedifference in the performance of technical trading may be attributed to acombination of the demand/supplymechanism in the cocoa market and an accident al influence of the Pound- Dollarexchange rate, reinforcing trendsin the LIFFE cocoa futures but weakening trends in the CSCE cocoa futures. Ourcase-study suggests a connectionbetween the succes or failure of technical trading and the relative magnitudesof trend and volatility of theunderlying series.
Keywords: 330; technical trading strategies; commodity futures; exchange rate; Kakaomarkt; Rohstoffderivat; Welt